Menopause-related changes to maxillary trabecular bone micro-architecture - Stein, Alexandra; Levit, Michael; Shah, Hammaad; Yin, Michael; Wadhwa, Sunil (Frontiers in Aging, 2025)
The number of midlife women seeking orthodontic treatment has significantly increased over the past 40 years. With this rise, orthodontists need to consider the potential impact of menopause on treatment planning. There have been no recent published studies on maxillary trabecular bone changes in humans related to menopause. This study aimed to explore the subject further. This cross-sectional cohort study was composed of qualifying participants with diagnostic maxillary CBCT images who were separated by self report into pre- (N = 21) and postmenopausal (N = 19) groups. The regions of interest were the trabecular bone of the incisive foramen and maxillary tuberosity. All scans were converted into binary images in order to draw all parametric and ratio raw data. The parameters of interest included trabecular bone volume fraction (BVF), trabecular thickness, trabecular number, and trabecular separation. In the incisive foramen subgroup, postmenopausal women showed a significant increase in trabecular separation (0.60 ± 0.25 to 0.84 ± 0.31 mm, P < 0.06). For the maxillary tuberosity subgroup, significant decreases in BV/TV (32.58 ± 15.85 to 17.63 ± 14.38 %, P <0.004), trabecular bone surface/tissue volume (2.66 ± 1.01 to 1.43 ± 1.09 %, P < 0.001) and trabecular separation (0.91 ± 0.39 to 1.58 ± 0.51 mm, P < 0.001) were observed. The findings reveal statistically significant differences in maxillary bone density at the level of the maxillary tuberosity and incisive foramen demonstrated in women who are of preversus post-menopausal status.